PENGARUH RELIGIUSITAS DAN SKALA KECERDASAN BUDAYA TERHADAP ETHNOSENTRISME KONSUMEN BAGI PRODUK ASING 2019 - Hatimy Paulin Doerleben; Made Siti Sundari (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2020)
This study seeks to understand the complicated relationship between religiosity and ethnocentrism of consumers by examining the mediating variable of cultural intelligence. The empirical model involves a structural equation model (SEM) with a data collection of 684 internet-user respondents. The results show that there was a positive impact of religiosity on consumer Ethnocentrism. In addition, the results also indicate that cultural intelligence strengthens the relationship between religiosity and ethnocentric consumerism. Overall, this study extends the discussion on cultural identity that incorporate into Ricardian model of international trade.